(untitled) (Indian Journal of Animal Production and Management, 2024)
Present study was carried out in Pahalgam and Sonmarg area of district Anatnag and Ganderbal respectively. A total of 200 respondents were selected using grab sampling technique, from Pahalgam 80 respondents were selected and from Sonmarg 120 respondents. An interview schedule was developed and pretested to collect information on the socio economic aspects of Bakarwals. It was observed that majority of Bakarwals belonged to the age group of 40-59 years, who were illiterate and maintained family size of 4-5 members. Since the respondents were pastoralists 94%of them were landless with maximum pack size of 1-6 animals. Other livestock maintained by pastoralist it was observed maximum respondents are having upto 250 animals. Primary occupation of the respondents (95.00%) was rearing of small ruminants with only (5.00%) having primary occupation based on agriculture. Sub occupation included providing equines on rent either for work or yatra. A considerable number of respondents (52%) are having monthly income of Rs 11000 -20000/.